The effects of high temperature on breeding characteristics and the living strength of the Japanese Quails (Coturnix Coturnix Japonica) - Özbey, Orhan; Yildiz, Nihat; Esen, Fikret (My University, 2006)
In this study, it was aimed to determine the effects of high temperature on the live weight, food consumption, taking benefit from the food, living strength, some carcass characteristics and the respective effects on the living strength. By this purpose, 584 quails at the age of 1 week were separated into two groups; one of the groups was identified as the control group to be placed under variable temperature (18-24°C), and the other group (trial group) was kept under 35°C. As a result of the research, the differences between the control and trial groups regarding to the live weight, carcass weight and carcass productivity, food consumption and the values of taking benefit from the food were found significant. (P<0.05, P<0.01). Depending on the higher temperatures, some decreases were found in the live weight, food consumption and the values of taking benefit from the food, living strength. © Asian Network for Scientific Information, 2006.
Keywords: Body weight; Carcass features; Food consumption; Food efficiency; High temperature; Quail; Survivality